2011
DOI: 10.1111/j.1365-2753.2011.01711.x
|View full text |Cite
|
Sign up to set email alerts
|

Using vote cards to encourage active participation and to improve critical appraisal skills in evidence‐based medicine journal clubs

Abstract: We suggest the regular and routine use of vote cards in EBM journal clubs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…The argumentation of this Editorial Introduction and the 41 papers of this issue [43–83] together constitute the 13th thematic edition of the Journal of Evaluation in Clinical Practice , building upon the work of the previous 12 [12–23]. We have entitled this year's edition ‘Models in the Balance: Evidence‐based Medicine versus Evidence‐informed Individualised Care’, because we believe that the time is now right to institute a debate on the need to progress towards the formulation of personalized models of care informed , but not based , on the E of EBM, representing a Hegelian shift in understanding following some 20 years of intensive philosophical and clinical argumentation on the nature of knowledge and action in clinical practice.…”
Section: Resultsmentioning
confidence: 99%
“…The argumentation of this Editorial Introduction and the 41 papers of this issue [43–83] together constitute the 13th thematic edition of the Journal of Evaluation in Clinical Practice , building upon the work of the previous 12 [12–23]. We have entitled this year's edition ‘Models in the Balance: Evidence‐based Medicine versus Evidence‐informed Individualised Care’, because we believe that the time is now right to institute a debate on the need to progress towards the formulation of personalized models of care informed , but not based , on the E of EBM, representing a Hegelian shift in understanding following some 20 years of intensive philosophical and clinical argumentation on the nature of knowledge and action in clinical practice.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, many advanced educational and training programs have adopted different methods and modules to integrate critical appraisal skills in their curriculum using EBP methodology. 1,[3][4][5][8][9][10][11] However, no consensus on a standard model has emerged. Although a different approach, our findings were consistent with Moher, 4 who found that an evidence-based medicine curriculum improved residents' performance after attending at least six journal club sessions.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, pedagogical studies looking at the effectiveness of the journal club approach in health care education have mainly focused on the advantages, periodicity, and article selection. [1][2][3][4][5][6][7][8][9] Numerous models have been published on how to establish and conduct journal clubs. 1,[3][4][5][8][9][10][11] However, none of these presented a specific validated tool or applied evidence-based practice (EBP) to develop a systematic approach to critical appraisal or research design evaluation.…”
Section: Introductionmentioning
confidence: 99%
“… 1 – 3 However, many challenges are encountered when designing an effective journal club structure that actively engages learners and accomplishes these objectives. 4 , 5 , 6 Most programs assign designated residents to deliver an oral presentation, 7 while the remainder of the participants have little motivation to prepare beforehand and risk becoming passive listeners. The traditional Socratic method of “calling on” residents may encourage participation, but may also conflict with the desire to create a collegial atmosphere.…”
Section: Introductionmentioning
confidence: 99%